Quantitative analysis component : on the determinants of innovation in services and its linkages with productivity - Tello, Mario D. (CISEPA-PUCP, 2021)
Analysis of services sector and innovation activities taken separately are scanty for Peruvian economy 1 and taken together not existent. The average share of real value added of the services sector out of GDP in Peru in the last decade has been about 40% (Banco Central de Reserva Del Peru, 2012) and the estimated employment share out of total occupied economic active population (OEAP) about 32%, wherein 77% of this employment comes from the informal sector. Most of the work on the services sector has been oriented to the analysis of export of services, in particular on the tourism sector (Tello, 2012b).